Service quality and customer satisfaction: a study at Perbendaharaan Malaysia Sarawak / Abang Nurfadli Abang Yusuf & Mohd. Taufiq Ahmad Jerry - Abang Yusuf, Abang Nurfadli (2013)
Service quality plays important roles in nowadays organization. Customer service is a key factor in achieving organization success. It can either make or break your organization. Every organization management must recognize the reality that customer service is imperative in the success of their organization. This will ensure your customer's satisfaction and commitment to your organization. Your ability to focus on your consumer's need rather than your own and servicing them to the best of your ability will ensure that your organization will be far more cost-effective than you have ever dreamed of. This research study focuses on the determinants of customer satisfaction on service quality. The study will take place at Perbendaharaan Malaysia Sarawak.